2020
DOI: 10.1007/s11060-020-03574-w
|View full text |Cite
|
Sign up to set email alerts
|

Distinct topographic-anatomical patterns in primary and secondary brain tumors and their therapeutic potential

Abstract: Purpose Understanding the topographic-anatomical patterns of brain tumors has the potential to improve our pathophysiological understanding and may allow for anatomical tailoring of surgery and radiotherapy. This study analyzed topographic-anatomical patterns underlying neuroepithelial tumors, primary CNS lymphoma and metastases. Methods Any histologically confirmed supra- or infratentorial parenchymal neoplasia of one institution over a 4-year period was included. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…The dependence on histopathology only consists of metastases as negative driver and astrocytoma as well as WHO grade I as positive drivers. A plausible explanation is the unequal prevalence of the different tumor types with predominance of glioblastoma, metastases and astrocytoma ( Akeret et al, 2020 , Siegel et al, 2020 ). Certain cerebellar structures, such as the cerebellar subcortical white matter and the inferior semilunar/gracile lobules influence the prediction in the direction of “seizures”.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dependence on histopathology only consists of metastases as negative driver and astrocytoma as well as WHO grade I as positive drivers. A plausible explanation is the unequal prevalence of the different tumor types with predominance of glioblastoma, metastases and astrocytoma ( Akeret et al, 2020 , Siegel et al, 2020 ). Certain cerebellar structures, such as the cerebellar subcortical white matter and the inferior semilunar/gracile lobules influence the prediction in the direction of “seizures”.…”
Section: Discussionmentioning
confidence: 99%
“…However, assuming a causal relationship would be a wrong conclusion, as the inference analysis provided strong evidence against it. The fact that a subcortical cerebellar location in the inferior semilunar/gracile lobule is the most frequent manifestation of cerebellar metastases ( Akeret et al, 2020 ) might be an explanation for the dependence of the model on these variables. The associated risk of concomitant supratentorial metastases and thus an increased risk of seizures might create this dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, analyses mapping the distribution of BMs were conducted using MRI voxel-based methods, and certain associations between BMs locations and primary malignancies were found. The preferred localization of BMs at the grey-white matter junction and the watershed regions had been well documented, which was explained by the trapping of tumor emboli in the terminal supply areas of large intracranial arteries [ 9 , 10 , 11 ]. Further investigations regarding voxel-based landscapes of BM sites similarly demonstrated that the posterior fossa was a predilection watershed site of BMs from lung and breast cancers [ 10 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specific anatomical patterns are seen for example in inflammatory conditions such as amyotrophic lateral sclerosis (Bede et al 2016) or autoimmune encephalitis (Dalmau and Graus 2018). Different brain tumors show distinct topographic anatomical patterns (Akeret et al 2020). The brain also exhibits an anatomically selective vulnerability to metabolic disease (Patel 1994) or toxic injury (Valk and van der Knaap 1992).…”
Section: Introductionmentioning
confidence: 99%